The novel mechanism facilitating chronic hepatitis B infection: immunometabolism and epigenetic modification reprogramming - Wang, Zhengmin; Liu, Nan; Yang, Yang; Tu, Zhengkun (Frontiers in Immunology, 2024)
Hepatitis B Virus (HBV) infections pose a global public health challenge. Despite extensive research on this disease, the intricate mechanisms underlying persistent HBV infection require further in-depth elucidation. Recent studies have revealed the pivotal roles of immunometabolism and epigenetic reprogramming in chronic HBV infection.Immunometabolism have identified as the process, which link cell metabolic status with innate immunity functions in response to HBV infection, ultimately contributing to the immune system's inability to resolve Chronic Hepatitis B (CHB). Within hepatocytes, HBV replication leads to a stable viral covalently closed circular DNA (cccDNA) minichromosome located in the nucleus, and epigenetic modifications in cccDNA enable persistence of infection. Additionally, the accumulation or depletion of metabolites not only directly affects the function and homeostasis of immune cells but also serves as a substrate for regulating epigenetic modifications, subsequently influencing the expression of antiviral immune genes and facilitating the occurrence of sustained HBV infection. The interaction between immunometabolism and epigenetic modifications has led to a new research field, known as metabolic epigenomics, which may form a mutually reinforcing relationship with CHB. Herein , we review the recent studies on immunometabolism and epigenetic reprogramming in CHB infection and discuss the potential mechanisms of persistent HBV infection. A deeper understanding of these mechanisms will offer novel insights and targets for intervention strategies against chronic HBV infection, thereby providing new hope for the treatment of related diseases.